The role of investment in stimulating economic activity - the Kurdistan Region of Iraq as a model for the period (2006-2021) - Ibrahim, Bahjat; Ahmed, Dildar; Al-Saffar, Ahmed (Humanities Journal of University of Zakho, 2022)
The paper aims to identify the theoretical side of investment, in addition (to show) showing the role of investment in stimulating the economics of Kurdistan reign of Iraq during the research period and analyzing its contribution in activating all the economics sectors and defining the obstacles and difficulties facing the investment proses in the region. The research problem was if the investment in the region contributed in stimulating the economic activity during the research period, based on primes that the role of the investment in the reign is positive but at the same time has minor effect. The research concluded that the role of investment has raised after issuance law (4) in 2006, in which it increased approximately to %784 in 2007. However, there was a lake in applying the law that lade most of the investment activities to the distribution and (service) activities. In other words, all the economic activities that have been invested in were nonprofitable investments and has not any real contribution in the economic activities, in addition to difficulties in determining the fluctuation in relationship between the investment and GDP. The research suggested reconsidering in the investment law (4) and adjusted it in which it should direct the investment proses to exploit the economic resources and increase the real gross production through the productive economic sectors.